Blending Internet-of-Things (IoT) solutions into relationship marketing strategies - Lo, Fang-Yi; Campos, Nayara (Technological forecasting & social change, 2018)
With contemporary life becoming more instantly connected and as the disruptiveness of technologies is occurring at a faster pace, the Internet-of-Things (IoT) is now even more accessible and common, prompting companies to adopt IoT solutions to improve their customers' experiences. IoT enables physical devices to connect and exchange data through the Internet by collecting strategic information, thus creating opportunities for companies to become more efficient and responsive to market changes. This paper thus investigates how companies are blending IoT solutions into their relationship marketing strategies and focuses on finding how this combination can boost business performance and what the challenges are when dealing with disruptive technology changes. To explore the subject's detailed information and to get a better understanding of managerial decisions concerning IoT, this research conducts in-depth case design analysis from a company's point of view. The data presented herein come from two main sources: open-ended interviews and direct observations, with the interviewees holding high managerial positions in Taiwan's IoT industry. This study aims to contribute to the literature by bringing awareness to the importance of closely following technological trends in combination with relationship marketing strategies and how they help firms remain competitive and profitable. The results of this empirical research shed light on the importance of understanding the impacts of IoT solutions on businesses, especially on clients' behaviors and the development of targeted strategies. The cases herein present similarities on the awareness of the speed of disruptive technologies like IoT, the importance of developing new solutions aligned with new technologies, their impact at creating new business solutions, and their contribution to the development of firm strategies. The findings also show that the application of innovative IoT solutions positively affects the process of developing long and successful relationships through relationship marketing actions. Conversely, concerns related to data security vary according to business segments and relationship marketing pillars such as trust, commitment, and reliability, which could help reduce feelings of ambiguity. This research contributes to filling the gap in the literature by offering a deeper understanding of the correlation between IoT and relationship marketing. Moreover, we illustrate how a combination of these two factors can contribute to the development of stronger marketing strategies, as well as their implications on business. The results of this research suggest further and more comprehensive investigations are needed in the future in order to explore the topic in greater depth and to see how the speed of technology is evolving. •Companies should blend IoT solutions into relationship marketing strategies.•This combination can boost business performance and overcome challenges when dealing with disruptive technology changes.•Innovative IoT solutions help develop long and successful consumer relationships through relationship marketing actions.